APJ as Promising Therapeutic Target of Peptide Analogues in Myocardial Infarction- and Hypertension-Induced Heart Failure - Daniela Rossin; Roberto Vanni; Marco Lo Iacono; Caterina Cristallini; Claudia Giachino; Raffaella Rastaldo (MDPI AG, 2023)
The widely expressed G protein-coupled apelin receptor (APJ) is activated by two bioactive endogenous peptides, apelin and ELABELA (ELA). The apelin/ELA-APJ-related pathway has been found involved in the regulation of many physiological and pathological cardiovascular processes. Increasing studies are deepening the role of the APJ pathway in limiting hypertension and myocardial ischaemia, thus reducing cardiac fibrosis and adverse tissue remodelling, outlining APJ regulation as a potential therapeutic target for heart failure prevention. However, the low plasma half-life of native apelin and ELABELA isoforms lowered their potential for pharmacological applications. In recent years, many research groups focused their attention on studying how APJ ligand modifications could affect receptor structure and dynamics as well as its downstream signalling. This review summarises the novel insights regarding the role of APJ-related pathways in myocardial infarction and hypertension. Furthermore, recent progress in designing synthetic compounds or analogues of APJ ligands able to fully activate the apelinergic pathway is reported. Determining how to exogenously regulate the APJ activation could help to outline a promising therapy for cardiac diseases.